Résister au monde. Déclinaisons historiques de l’identité contemporaine dans quelques romans de Véronique Bergen - Zbierska-Mościcka, Judyta (Wydawnictwo Naukowe UAM, 2013)
Fictional autobiographies of a Belgian writer, Véronique Bergen, describing fates of outstanding characters albeit marginalised by history (Kaspar Hauser, Ludwig II of Bavaria, Ulrike Meinhof), may be interpreted as a metaphor of a contemporary man’s fate, a man caught, often against his will, in a course of political or social events. The characters described here adopt an active resistance stand against life, the stand defined by Bergen in her essay "Résistances philosophiques", and manifested by striving to create one’s own, coherent world and a new language. In her reference to G. Deleuze, the author states that the said resistance is not only an act of existence but, also, an act of creation while creation of a new language involves, mainly, building of one’s own “I’. Identity of an individual is entangled within identity of a creator while reflection on language – with reflection on artistic medium.
Resisting the world. Historical declinations of contemporary identity in some Véronique Bergen’s novels
Keywords: fictional autobiography; History; resistance; language; Véronique Bergen